2008
DOI: 10.1002/pssa.200723484
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and electrical properties of ultra‐thin silicon nanowires

Abstract: Ultra thin (8 nm) silicon nanowires have been fabricated by Atomic Force Microscopy (AFM) lithography on an insulator layer starting from Silicon On Insulator (SOI) substrates. Electrical measurements reveal a high sensitivity of the electron transport in these ultra thin wires to the charge trapping on the Si/SiO2 interface states. (© 2008 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Consequently, the nanowires displayed a 3-fold greater resistance to re-oxidation when exposed to ambient conditions. The Si nanowires also showed higher stability compared to 2D Si (111) surfaces, despite having a lower surface coverage. Haick and co-workers further observed the Table 1 Bifunctional cross-linker molecules used for Si nanowire functionalisation rate of alkylation to be greater for Si nanowires.…”
Section: Properties Of Functionalised Nanowires 51 Stability Of Funct...mentioning
confidence: 95%
See 3 more Smart Citations
“…Consequently, the nanowires displayed a 3-fold greater resistance to re-oxidation when exposed to ambient conditions. The Si nanowires also showed higher stability compared to 2D Si (111) surfaces, despite having a lower surface coverage. Haick and co-workers further observed the Table 1 Bifunctional cross-linker molecules used for Si nanowire functionalisation rate of alkylation to be greater for Si nanowires.…”
Section: Properties Of Functionalised Nanowires 51 Stability Of Funct...mentioning
confidence: 95%
“…Ge forms stable oxides in the 2+ (GeO) and 4+ (GeO 2 ), oxidation states, the latter of which is water soluble. Schmeisser 32 was the first to carry out synchrotron studies of oxidised Ge (100) and (111) surfaces and found the presence of all four Ge oxidation states. The oxidation behaviour of Ge is strongly dependant on the oxidative environment and is influenced by illumination conditions and crystal orientation.…”
Section: Oxidation Of Ge Nanowiresmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, by controlling SiNW surface functionalization, it is also possible to inhibit non-specifi c interactions, improve blood circulation (PEG-spacer) and increase electrical properties (defect passivation). 16,25,[27][28][29][30][31] …”
Section: Modifi Cation Of Hydrogen-terminated Sinwmentioning
confidence: 99%